1999
DOI: 10.1111/j.1439-0507.1999.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of fluconazole in the long‐term suppressive therapy of fungal infections in patients with artificial implants

Abstract: With the increased use of artificial implants the management of related infections has become an important challenge. Normally an infected implant would be removed. In many cases this might be contraindicated and drug treatment remains as the only alternative. As microbiological eradication is often impossible, especially in fungal infections at artificial implants (FIAI) long-term suppressive therapy might be required. The objective of this study was to determine the therapeutic value of fluconazole (F) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…For instance, Walsh et al reported that C. neoformans could form biofilms in ventriculoatrial shunt catheters (35). In addition, several reports of C. neoformans infection of polytetrafluoroethylene peritoneal dialysis fistula and prosthetic cardiac valves highlight the ability of this organism to adhere to medical devices (6,7,26). In fact, the increasing use of ventriculoperitoneal shunts to manage intracranial hypertension associated with cryptococcal meningoencephalitis highlights the importance of investigating the biofilm-forming properties of this organism (2,13).…”
mentioning
confidence: 99%
“…For instance, Walsh et al reported that C. neoformans could form biofilms in ventriculoatrial shunt catheters (35). In addition, several reports of C. neoformans infection of polytetrafluoroethylene peritoneal dialysis fistula and prosthetic cardiac valves highlight the ability of this organism to adhere to medical devices (6,7,26). In fact, the increasing use of ventriculoperitoneal shunts to manage intracranial hypertension associated with cryptococcal meningoencephalitis highlights the importance of investigating the biofilm-forming properties of this organism (2,13).…”
mentioning
confidence: 99%
“…5 Especially in prosthetic tissues, the environmental factors are optimal in creating a nucleus for growth, aggregation, and ramification of mycelium. 6,7 In our patient, the Candida infection caused acute obstruction of the prosthetic ureter by forming fungus balls. obstructing the lumen of the prosthesis completely.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we think that fluconazole therapy has no place in treating acute FE. However, there is increasing evidence that fluconazole could be administered as suppressive therapy to patients who successfully completed a full course of amphotericin B [47]. Animal studies have demonstrated that fluconazole combined with cyclosporine has a fungicidal effect superior to amphotericin B [48].…”
Section: Therapymentioning
confidence: 98%
“…Chronic suppressive therapy of FE with oral fluconazole is increasingly used [47,50,51], although the efficacy of this strategy has never been proven. However, many patients, especially those who were not candidates for surgical interventions, were treated successfully for long periods with oral fluconazole after having completed a full course of amphotericin B.…”
Section: Therapymentioning
confidence: 99%